(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Infertility was define as; a disease characterized by the failure to establish a clinical pregnancy after 12 months of regular unprotected sexual intercourse, or due to an impairment of a person’s capacity to reproduce, either as an individual or with his/her partner. According to the latest definition by the international glossary on infertility and fertility care, regular sexual intercourse is an important determinant for the occurrence of pregnancy. Aim of the study: To assess the relation between Coenzyme Q10 level in the follicular fluid with oocyte maturity, fertilization rate, embryo grading, and pregnancy rate Patients and method: A prospective cross sectional study conducted at the High Institute for Infertility Diagnosis and Assisted Reproductive Technologies / Al-Nahrain University and in fertility center at AlSadr general hospital during the period from December 2019 to August 2020. Sixty infertile couples were enrolled in this study; all underwent ICSI cycles Results: Mean level of Co Q10 in Grade III and IV (0.387 ± 0.54) than that in Grade I and II (0.539 ± 0.65), CoQ10 total in pregnant were 0.79 ± 0.63 and in non-pregnant were 0.381 ± 0.2, A threshold of 0.27 of CoQ10 had a sensitivity of 80.0% and specificity of 67.0 %, PPV was (88.0%), NPV (45%) and accuracy was (74%). ROC curve of CoQ10 for pregnancy prediction Conclusion: Significant decrease of Co Q10 between in Grade III and IV than that in Grade I and II. CoQ10 total were increase in pregnant women than non-pregnant.